2005
DOI: 10.1182/blood.v106.11.814.814
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Radiation Dose Levels after EBVP Regimen in Favorable Supradiaphragmatic Clinical Stages (CS) I-II Hodgkin’s Lymphoma (HL): Preliminary Results of the EORTC-GELA H9-F Trial.

Abstract: Preventing late toxicity has become the cornerstone in the management of HL as global results greatly improved regarding event-free (EFS) and overall survival (OS) rates. With this aim, the EORTC and GELA groups conducted a trial (H9-F) comparing three radiation doses in patients in complete remission (CR/CRu) after chemotherapy. Adult patients with supradiaphragmatic CS I-II HL and favorable features (age < 50, and CS I-II2–3, and A + ESR < 50 or B + ESR < 30, and MT ratio < 0.35) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…In the EORTC-GELA H9-F study for early favorable Hodgkin's lymphoma investigating reduction or omission of IFRT following complete remission to EBVP (epirubicin, bleomycin, vinblastine, and prednisone), no differences were seen between 20 and 36 Gy radiation on interim analysis [21]. However, the no-RT arm was closed due to excess relapse [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the EORTC-GELA H9-F study for early favorable Hodgkin's lymphoma investigating reduction or omission of IFRT following complete remission to EBVP (epirubicin, bleomycin, vinblastine, and prednisone), no differences were seen between 20 and 36 Gy radiation on interim analysis [21]. However, the no-RT arm was closed due to excess relapse [21].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results of the EORTC‐GELA H9‐F trial were reported in abstract form [29]. This trial randomized early‐stage patients with HL and favourable features to chemotherapy alone with epirubicin, bleomycin vinblastine and prednisone (EBVP), EBVP and 20 Gy involved field radiation therapy (IF RT) or EBVP and 36 Gy IF RT.…”
Section: Chemotherapy Alone In the Treatment Of Nonbulky Early Stagesmentioning
confidence: 99%
“…Preliminary results of the EORTC-Groupe d'Etude des Lymphomes de l'Adulte H9-F trial were recently reported [24]. That trial, conducted after 1999 and recently closed, randomized early-stage HL patients with favorable features to chemotherapy alone with EBVP, EBVP plus 20 Gy IFRT, or EBVP plus 36 Gy IFRT.…”
Section: Chemotherapy Alone In the Treatment Of Nonbulky Early-stage Hlmentioning
confidence: 99%